Microbiology of respiratory system infections - Kon, Kateryna; Rai, Mahendra (London : Academic Press, 2016)
The Microbiology of Respiratory System Infections reviews modern approaches in the diagnosis, treatment, and prophylaxis of respiratory system infections. The book is very useful for researchers, scientists, academics, medical practitioners, graduate and postgraduate students, and specialists from pharmaceutical and laboratory diagnostic companies. The book has been divided into three sections according to the types of respiratory pathogens. The first section contains reviews on the most common and epidemiologically important respiratory viruses, such as influenza virus, severe acute respiratory system coronavirus, and recently discovered Middle East respiratory syndrome coronavirus. The second section is devoted to bacterial and fungal pathogens, which discusses etiology and pathogenesis including infections in patients with compromised immune system, and infections caused by fungal pathogens, such as Aspergillus and Pneumocystis. The third section incorporates treatment approaches against different types of bacterial infections of the lower respiratory tract. This section reviews classical antimicrobial and phytomedical approaches as well as the application of nanotechnology against respiratory pathogens.
1 Influenza virus infections: clinical update, molecular biology, actual therapeutic options and experimental pharmacology; 2 Influenza viral infection in respiratory system - potential ways of monitoring; 3 SARS coronavirus infections of the lower respiratory tract and their prevention; 4 The MERS-CoV respiratory infection: An emerging infection from the Arabian peninsula; 5 Respiratory infections of the human bocavirus (HBoV); 6 Circulation of respiratory pathogens at mass gatherings; 7 Indoor air pollution due to mycoflora causing acute lower respiratory infections; 8 Is there a connection between respiratory allergens and parasitism?; 9 United airways: The voyage from rhinitis andrhinosinusitis to lower airway diseases; 10 Paediatric chronic lung infections; 11 Respiratory infections in patients with hematological malignancies; 12 Pulmonary infections in recipients of various forms of hematopoietic stem cell transplantation; 13 Pseudomonas aeruginosa producing metallo beta lactamase as an opportunistic pathogen in lung infection; 14 Mycobacterium tuberculosis: Clinical and microbiological aspects; 15 Pulmonary Aspergillosis; 16 Laboratory diagnosis of Pneumocystis jirovecii pneumonia; 17 Antimicrobial approaches against bacterial pathogens which cause lower respiratory system infections; 18 Role of nanotechnology in controlling pulmonary infections; 19 Management of lower respiratory infections by essential oils and plant extracts; 20 Natural compounds in the treatment of respiratory infections; 21 Current therapeutics and prophylactic approaches to treat pneumonia
Includes bibliographical references and index.
Print version record.
Keywords: Respiratory infections -- Microbiology; Medical microbiology; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Medical microbiology; Respiratory System -- microbiology; Electronic books